2020
DOI: 10.1016/j.transci.2020.102949
|View full text |Cite
|
Sign up to set email alerts
|

Three non-classical mechanisms for anemic disease of the fetus and newborn, based on maternal anti-Kell, anti-Ge3, anti-M, and anti-Jra cases

Abstract: Maternal alloantibody-mediated hemolytic disease of the fetus and newborn (HDFN) ranges from no or mild symptoms to severe hydrops and intrauterine fetal demise. Hemolytic anti-D-mediated HDFN proceeds via a longknown mechanism, to which three other pathways to fetal/neonatal anemia may be added: (0) Fetal erythrocyte destruction can proceed by extravascular phagocytosis. (1) An apoptotic pathway has been described for anti-Kell, and anti-Ge3. (2) Erythropoietic suppression may arise from altered or deformed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…In addition to the generalizable advantages of monoclonal antibody therapy (e.g., cost-effective, scalable, high specificity, lot-to-lot consistency), the substantial advances in antibody technology and increased understanding of immune function, now allow antibodies to be engineered to have increased affinity for the neonatal Fc receptor (FcRn), thereby facilitating an extended half-life to make passive immunization more durable. Moreover, antibodies can be engineered to inhibit antibody:FcRn interactions at the maternal-fetal interface, which is especially important for preventing hemolytic disease of the fetus and newborn mediated by alloantibodies to non-D RBC antigens ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the generalizable advantages of monoclonal antibody therapy (e.g., cost-effective, scalable, high specificity, lot-to-lot consistency), the substantial advances in antibody technology and increased understanding of immune function, now allow antibodies to be engineered to have increased affinity for the neonatal Fc receptor (FcRn), thereby facilitating an extended half-life to make passive immunization more durable. Moreover, antibodies can be engineered to inhibit antibody:FcRn interactions at the maternal-fetal interface, which is especially important for preventing hemolytic disease of the fetus and newborn mediated by alloantibodies to non-D RBC antigens ( 39 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Other antibodies known to cause erythropoietic suppression include anti-K, anti-Ge3, and anti-M via different mechanisms including antibody-mediated apoptosis and alteration of the red cell surface. 24 Our results initiate a mechanistic understanding of anti-Jr a mediated suppression, but confirmation of these findings and further investigations to better elucidate the mechanism are needed. Interestingly, like other case reports, the first child in our case who had possible anti-A and/or anti-Jra mediated HDFN had a positive IgG and C3 DAT.…”
Section: Discussionmentioning
confidence: 64%
“…26 Although maternal anti-M IgG titers are often quite low, there is chronic transplacental transfer of maternal IgG into fetal circulation throughout the course of pregnancy, with ongoing cumulative adverse effects. 27 Glycophorin A is expressed on early erythroid precursors and it is believed that anti-M binding may lead to ineffective erythropoiesis and reticulocytopenia similar to that reported for anti-K, 24,27 but with a distinct target molecule. This was demonstrated by Ishida et al who showed a decrease in erythroid colony formation by anti-M in vitro.…”
Section: Discussionmentioning
confidence: 79%